2021
DOI: 10.1155/2021/5548130
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab‐Induced Mitochondrial Dysfunction, Endoplasmic Reticulum Stress, and ERK Inactivation Contribute to Cardiotoxicity

Abstract: The molecular mechanisms underlying the cardiotoxicity associated with bevacizumab, a first-line immunotherapeutic agent used to treat lung cancer, are not fully understood. Here, we examined intracellular signal transduction in cardiomyocytes after exposure to different doses of bevacizumab in vitro. Our results demonstrated that bevacizumab significantly and dose-dependently reduces cardiomyocyte viability and increases cell apoptosis. Bevacizumab treatment also led to mitochondrial dysfunction in cardiomyoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 69 publications
0
11
1
1
Order By: Relevance
“…Induction of acute ER stress using thapsigargin impairs mitochondrial function in mouse and rat hearts [ 3 , 4 , 5 ]. An increase in ER stress with doxorubicin or bevacizumab treatment also results in mitochondrial dysfunction [ 6 , 7 ]. Mitochondrial dysfunction contributes to cardiac injury in many pathological conditions including aging and heart failure [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Induction of acute ER stress using thapsigargin impairs mitochondrial function in mouse and rat hearts [ 3 , 4 , 5 ]. An increase in ER stress with doxorubicin or bevacizumab treatment also results in mitochondrial dysfunction [ 6 , 7 ]. Mitochondrial dysfunction contributes to cardiac injury in many pathological conditions including aging and heart failure [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yue Li et al. demonstrated that bevacizumab-mediated cardiotoxicity is associated with mitochondrial dysfunction and ERK pathway inactivation ( 31 ). Rituximab has also been shown to cause adverse cardiac events including arrhythmia and, on occasion, myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…A cell viability test was performed by CCK‐8 kit to evaluate the proliferation of SCLC cells under pazopanib treatment, as previously described 19 . In brief, 5 × 10 3 cells/well were cultured in 96‐well plates in 180 μl of complete medium.…”
Section: Methodsmentioning
confidence: 99%
“…A cell viability test was performed by CCK-8 kit to evaluate the proliferation of SCLC cells under pazopanib treatment, as previously described. 19 In brief, 5 Â 10 3 cells/well were cultured in 96-well plates in 180 μl of complete medium. Different concentrations of pazopanib in 20 μl of complete medium were added to each well (range 0-30 μM).…”
Section: Cell Proliferation Assaymentioning
confidence: 99%